Monoclonal antibody that recognizes an outer membrane antigen common to the pathogenic Neisseria species but not to most nonpathogenic Neisseria species. - Cannon, J G (1984)
A hybridoma derived from a mouse immunized with gonococcal outer membranes produced an antibody, designated H.8, that bound to all strains of Neisseria gonorrhoeae and N. meningitidis tested, and to N. lactamica and N. cinerea, but only rarely to other nonpathogenic Neisseria species. Studies with the gonococcal strain used in production of the antibody showed that the antibody bound to a surface-exposed, protease-sensitive, and heat-modifiable outer membrane antigen that we believe is distinct from previously described gonococcal outer membrane proteins.